2014
DOI: 10.1007/jhep06(2014)086
|View full text |Cite
|
Sign up to set email alerts
|

Holographic inflation and the conservation of ζ

Abstract: In a holographic description of inflation, cosmological time evolution in the bulk is expected to correspond to the renomalization group (RG) flow in a dual boundary theory. Here, we analyze this expectation by computing the correlation functions of the curvature perturbation ζ holographically. For this purpose, we use a deformed conformal field theory at the boundary, with a single deformation operator. In standard single field models of inflation, ζ is known to be conserved at large scales under very general… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
44
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(46 citation statements)
references
References 81 publications
(133 reference statements)
2
44
0
Order By: Relevance
“…The author is also interested in the possibility of its de Sitter space version, from the viewpoint of applications to primordial correlation functions in inflationary cosmology; in particular, decompositions of primordial correlators along the line of[15], holographic computations of non-Gaussianities using three-dimensional conformal perturbation theory like[16][17][18][19][20].…”
mentioning
confidence: 99%
“…The author is also interested in the possibility of its de Sitter space version, from the viewpoint of applications to primordial correlation functions in inflationary cosmology; in particular, decompositions of primordial correlators along the line of[15], holographic computations of non-Gaussianities using three-dimensional conformal perturbation theory like[16][17][18][19][20].…”
mentioning
confidence: 99%
“…However, the authors in [34] has shown that this is not the case in the dual CFT description. The requirement that higher correlators of ζ should be conserved restricts the possibilities for the RG flow.…”
Section: Discussionmentioning
confidence: 98%
“…Even if the gauge fields have a non-vanishing energy density, at the level of classical background this would be indistinguishable from the single-field model 11 . In order to extract information about the gauge field contribution, it is necessary to investigate its linear perturbation and its contribution to the scalar and tensor power spectra (higher order correlators, like the bispectrum, would give a further way to distinguish them).…”
Section: Isotropic Power Spectramentioning
confidence: 97%
“…For other application of holographic techniques to cosmology see for example[8][9][10][11][12][13][14][15][16][17][18][19].…”
mentioning
confidence: 99%